SEKOLAH GRATIS DAN MUTU SEKOLAH: STUDI KASUS DI SMAN 2 BABAT TOMAN MUSI BANYUASIN SUMSEL - Afriantoni, Afriantoni; Ibrahim, Ibrahim (Jurnal Dinamika Pendidikan, 2015)
This study aimed to describe in depth between the link of school policy and the school quality improvement. The method in this study is a qualitative method using the case study presented descriptively. This research was conducted at SMA Negeri 2 Babat Tomat Kabupaten Musi Banyuasin. Based on this study it was found that the First, free school policy can help the economy / ease the burden of school costs to be incurred by the parents. Second, the policy constraints of the application for free school educa-tion at SMAN 2 Babat Toman is not very effective, so that the students interest is not increasing, infrastructure is one of the obstacles in the implementation of free school education, how the quality of schools will be increased if it is not supported by facilities and complete infrastructure. Third, the quality of school education free SMAN 2 Babat Toman already realized well with regard to input, input turns unselected maximum, that is the students. Fourth, the implementation of free school education in Banyuasin, the quality of school SMAN 2 Babat Toman Muba Sumsel was not increased. This means that the implementation for free school education quality of school SMAN 2 Babat Toman was not increased.Keywords : free schools, school quality, case studies